An analysis of how the firm objective debate is reflected in financial textbooks and in the MVV statements of JSE TOP40 firms - Abdulrehman, Shayan Aslam (Department of Finance and Tax, 2016)
This study investigates whether the shareholder, stakeholder and customer-oriented theories on the objective of the firm are reflected in modern financial textbooks, and in the Mission, Vision, and Values statements of the JSE TOP40 firms. The literature review discusses the shareholder, stakeholder and customer-oriented theories of the firm, among others, and shows that there is no consensus between finance researchers on the objective of the firm, with opposing views presented. The research approach adopts qualitative analysis as the method for this study, as it is deemed to be suitable for pattern recognition in large sets of data. The data consisted of twenty financial textbooks, and the MVV statements of the JSE TOP40 firms. Both the data sets were analysed to identify the shareholder, stakeholder and customer-oriented objectives of the firm using the word frequency and coding queries in software NVivo. The finding in respect of financial textbooks indicates that seventeen textbooks advocated for a shareholder objective, two advocated for a stakeholder, and one for a customer-oriented objective of the firm. The JSE TOP40 firms' finding indicates that seventeen pursued a stakeholder objective, twelve pursued a customer-oriented objective, and eleven pursued a shareholder objective. The study establishes that the shareholder, stakeholder and customer-oriented theories of the firm's objective are reflected better in the MVV statements of JSE TOP40 firms, than in financial textbooks. This highlights a disconnection between financial textbooks, where the shareholder objective of the firm was found to be dominant, and the JSE TOP40 firms' findings where the debate concerning the three objectives was more evenly spread. This study recommends that South African academic authors should update their financial textbooks to reflect more emphasis on the stakeholder and customer-oriented theories of the firm's objectives, as being pursued by the JSE TOP40 firms.